Liver Transplantation for Acute Hepatic Failure Following Intentional Iron Overdose - Eça, Rosário (2023)
The majority of acute iron toxicity cases occur in young children from accidental ingestion. In adults, iron poisoning is rare and mostly due to intentional ingestion. Physicians, particularly those who do not routinely treat pediatric patients, are often unfamiliar with the clinical manifestation of iron poisoning, its management, and its potential for multiple organ failure, especially liver damage. Severe acute hepatotoxicity treated with liver transplantation is rare in adults, with very limited published literature. We report a case of a severe iron tablet overdose with suicidal intent that progressed to fulminant hepatic failure despite medical treatment, ultimately treated with liver transplantation.